The Thatung in Cap Ngo Meh (Lantern Festival) Ritual In Hakka Society in Singkawang, West Kalimantan-Indonesia - M. Ikhsan Tanggok (Refleksi: Jurnal Kajian Agama dan Filsafat, 2013)
Cap Ngo Meh and Thatung are two things that cannot be separated from the life of Hakka people in Singkawang. In each Cap Ngo Meh festival, the performance of Thatung is a must. Cap Ngo Meh festival would not be completed if there was no performance of Thatung. Thatung can help humans and otherwise humans also have to give gifts to him. Therefore,Thatung is a special performance in Cap Ngo Meh festival in Singkawang.The main purpose of this paper is to show the relationship between Thatung performance and Cap Ngo Meh festival in Singkawang. The function of Thatung performance in Cap Ngo Meh festival in Singkawang is not only to repel evil spirits that may affect humans, but also to promote economics, improving of popularity himself and tourism in Singkawang.DOI: 10.15408/ref.v13i5.918